THE ROLE OF COMPETENCY IN MEDIATING TRAINING AND KNOWLEDGE MANAGEMENT ON WORK ABILITY OF INDONESIA MIGRANT WORKERS IN TAIWAN - Muhammad Danial, R Deni; Hegia Sampurna, Rizki; Lestari Pujiastuti, Yanti; Hestiana, Siska (Penerbit Lafadz Jaya, 2024)
This paper studies the Work Ability of Indonesian migrant workers in Taiwan. The workability of these migrant workers is very low due to factors such as lack of appropriate training, knowledge mismatch, cultural and language challenges, non-ideal working conditions, lack of competency development, and mental and physical welfare problems. To increase the Work Ability of migrant workers, good training and knowledge management is needed. The influence of the Training and Knowledge Management program will be significant and optimal in increasing the Work Ability of migrant workers if it is through increasing Competency. This study used quantitative methods and was conducted on 210 migrant workers as respondents. The results of this study show that training has no direct effect on increasing the workability of migrant workers. However, training influences Work Ability through Competency. Knowledge Management has a direct impact on increasing Work Ability. However, Competency does not mediate the influence of Knowledge Management on Work Ability. This means that the training program will be useful in increasing Work Ability if it is mediated by increasing Competency. Good Knowledge Management can directly increase the Work Ability of migrant workers without having to increase Competency.